2019
DOI: 10.1016/j.xphs.2018.10.062
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Subcellular Semimechanism-Based Pharmacokinetic/Pharmacodynamic Model to Characterize Paclitaxel Effects Delivered by Polymeric Micelles

Abstract: A transit compartment model was widely and successfully applied to characterize the complex time course of cancer chemotherapeutic effects in vivo or in vitro. However, the underlying mechanisms were not quantitatively depicted. This study aimed to develop a semimechanism-based cellular pharmacokinetic/pharmacodynamic (PK/PD) model to characterize paclitaxel (PTX) effect delivered by PLGA-PEG micelles which was based on analysis of drug subcellular distribution, the tubulin assembly level, the cell cycle shift… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Importantly, cells undergoing AME-induced mesenchymal-like cell transition exhibit morphology similar to cells undergoing transforming growth factor beta (TGF-β) induced EMT, which have been shown to possess enhanced metastatic character compared to epithelial-like cancer cells, thus indicating that the AME platform induces development of metastasis. Notably, previous studies regarding cell transition and the related mechanisms required analysis of time course treatments of drugs or cytokines. For example, Haley et al revealed multiple altered transcription and epigenetic pathways associated with mesenchymal trans-differentiation in NSCLC through a time course study of TGF-β treatment . However, the AME platform produced similar stages of metastasis-related transition simultaneously, further supporting the conclusion that the deregulation of ECM over time and resulting development of metastasis can be effectively simulated.…”
Section: Results and Discussionmentioning
confidence: 96%
“…Importantly, cells undergoing AME-induced mesenchymal-like cell transition exhibit morphology similar to cells undergoing transforming growth factor beta (TGF-β) induced EMT, which have been shown to possess enhanced metastatic character compared to epithelial-like cancer cells, thus indicating that the AME platform induces development of metastasis. Notably, previous studies regarding cell transition and the related mechanisms required analysis of time course treatments of drugs or cytokines. For example, Haley et al revealed multiple altered transcription and epigenetic pathways associated with mesenchymal trans-differentiation in NSCLC through a time course study of TGF-β treatment . However, the AME platform produced similar stages of metastasis-related transition simultaneously, further supporting the conclusion that the deregulation of ECM over time and resulting development of metastasis can be effectively simulated.…”
Section: Results and Discussionmentioning
confidence: 96%
“…Pharmacokinetic/pharmacodynamic (PK/PD) models can be used to predict the optimal conditions for a drug carrier to maximize the antitumor effect of the encapsulated drug relative to the free drug (Rodallec et al, 2018). In such PK/PD models, the disposition of the free and encapsulated drugs is often described by compartment models which are linked to the tumor compartment via blood flow rates (Zheng et al, 2019). Using an appropriate cell‐kill kinetic PD model, the number of tumor cells can be expressed quantitatively as a function of the free concentration of drug in the tumor compartment.…”
Section: Introductionmentioning
confidence: 99%
“…2 Currently, the co-delivery of anti-cancer drugs has been developed by assistance of biodegradables nanoparticles (NPs) such as polylactic glycolic acid (PLGA) NPs. [3][4][5] PLGA NPs are one group of the commonly used polymers in manufacturing NPs thanks to their high adaptability to biological environments, ability to degrade into natural metabolites, lower toxicity and higher stability than that of liposomes and some other drug delivery systems. PLGA NPs also have the ability to modify their surface to prevent rapid absorption of this polymer by the reticuloendothelial system of the body.…”
Section: Introductionmentioning
confidence: 99%